2000
DOI: 10.1074/jbc.275.14.9996
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Adhesion Protein from the Crayfish Pacifastacus leniusculus, a Serine Proteinase Homologue Similar toDrosophila Masquerade

Abstract: A cDNA encoding a protein resembling masquerade, a serine proteinase homologue expressed during embryogenesis, larval, and pupal development in Drosophila melanogaster, was identified in hemocytes of the adult freshwater crayfish, Pacifastacus leniusculus. The crayfish protein is similar to Drosophila masquerade in the following aspects: (a) overall sequence of the serine proteinase domain, such as the position of three putative disulfide bridges, glycine in the place of the catalytic serine residue, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 38 publications
0
68
0
Order By: Relevance
“…All the amino acid sequences could be matched exactly to the previously cloned and characterized crayfish mas-like protein ( Fig. 2A) (17). The N-terminal amino acid sequence of the 65-and 63-kDa proteins had identical amino acid sequences from T102 to A106.…”
Section: Determination Of Amino Acid Sequencesmentioning
confidence: 65%
See 2 more Smart Citations
“…All the amino acid sequences could be matched exactly to the previously cloned and characterized crayfish mas-like protein ( Fig. 2A) (17). The N-terminal amino acid sequence of the 65-and 63-kDa proteins had identical amino acid sequences from T102 to A106.…”
Section: Determination Of Amino Acid Sequencesmentioning
confidence: 65%
“…An antiserum against the crayfish mas-like protein was made by first preparing a synthetic peptide, CFTPQDLRVRWVSGRSTS, corresponding to a portion of the 33-kDa band (the serine proteinase-like domain) of the crayfish mas-like protein as described by Huang et al (17). Briefly, the synthetic peptide was coupled to OVA (Sigma) using sulfo-m-maleimidobenzoyl-N-hydroxysulfosuccinimide ester (Calbiochem, La Jolla, CA) as a coupling agent and then was used for production of a rabbit antiserum.…”
Section: Ab and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Through interactions with PAP and proPO, these proteinase-like molecules may anchor proPO activation to the surface of microorganisms. A masquerade-like, clip-domain SPH from the crayfish Pacifastacus leniusculus may serve as an opsonin by associating with microbial cells and host hemocytes (Huang et al, 2000;Lee and Söderhäll, 2001). We have isolated three clip-domain serine proteinases from M. sexta, which cleave proPO at Arg 51 but require the SPHs to generate active PO.…”
Section: Introductionmentioning
confidence: 99%
“…There is at least one regulatory clip domain at the amino terminus of these enzymes. Clip domains, initially identified in the horseshoe crab proclotting enzyme (Muta et al, 1990), are frequently found in arthropod SPs and serine proteinase homologs (SPHs) (Jiang and Kanost, 2000;Huang et al, 2000;Ross et al, 2003;Christophides et al, 2002). We have purified three PAPs from M. sexta prepupae, which cleave proPO at Arg 51 and require two clip-domain SPHs to generate active PO.…”
Section: Introductionmentioning
confidence: 99%